A novel chemical genetic approach reveals paralog-specific role of ERK1/2 in mouse embryonic stem cell fate control - Hu, Liang; Xiao, Xiong; Huang, Wesley; Zhou, Tao; Chen, Weilu; Zhang, Chao; Ying, Qi-Long (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Mouse embryonic stem cell (ESC) self-renewal can be maintained through dual inhibition of GSK3 and MEK kinases. MEK has two highly homologous downstream kinases, extracellular signal-regulated kinase 1 and 2 (ERK1/2). However, the exact roles of ERK1/2 in mouse ESC self-renewal and differentiation remain unclear. Methods: We selectively deleted or inhibited ERK1, ERK2, or both using genetic and chemical genetic approaches combined with small molecule inhibitors. The effects of ERK paralog-specific inhibition on mouse ESC self-renewal and differentiation were then assessed. Results: ERK1/2 were found to be dispensable for mouse ESC survival and self-renewal. The inhibition of both ERK paralogs, in conjunction with GSK3 inhibition, was sufficient to maintain mouse ESC self-renewal. In contrast, selective deletion or inhibition of only one ERK paralog did not mimic the effect of MEK inhibition in promoting mouse ESC self-renewal. Regarding ESC differentiation, inhibition of ERK1/2 prevented mesendoderm differentiation. Additionally, selective inhibition of ERK1, but not ERK2, promoted mesendoderm differentiation. Discussion: These findings suggest that ERK1 and ERK2 have both overlapping and distinct roles in regulating ESC self-renewal and differentiation. This study provides new insights into the molecular mechanisms of ERK1/2 in governing ESC maintenance and lineage commitment, potentially informing future strategies for controlling stem cell fate in research and therapeutic applications.